Science, Decision and Value
VII, 213 p.
Keywords: This volume grew out of the papers and comments presented at the Fifth University of Western Ontario Philosophy Colloquium, October 31- November 2, 1969. The colloquium papers were delivered by P. Suppes, R. B. Braithwaite, C. W. Churchman, and J. S. Minas. Comments are provided from others attending the colloquium, with one reply by P. Suppes. Also included are papers recently published elsewhere by A. Michalos, P. Fishburn and H. -N. Castaneda. The editors express thanks to these authors and to the editors of the following respective journals for per mission to publish: Theory and Decision, Synthese, and Critica. Finally, there is an extensive bibliography of decision theory, vis-a. -vis science and values. The editors wish to thank the officers of the University of Western Ontario for making the colloquium possible. THE EDITORS CONTENTS PREFACE V PATRICK SUPPES I The Concept of Obligation in the Context of Decision Theory 1 HENR Y KYBURG I Comments 15 PATRICK SUPPES I Reply to Professor Kyburg 19 R. B. BRAITHWAITE I Behind Decision and Games Theory: Acting with a Co-Agent versus Acting Along with Nature 22 ISAAC LEVI I Comments 56 RONALD GIERE I Comments 62 I. J. GOOD I Comments 67 C. WEST CHURCHMAN I Measurement: A Systems Approach 70 ISAAC LEVI I Comments 87 RONALD GIERE I Comments 95 PETER C. FISHBURN I Utility Theory with Inexact Preferences and Degrees of Preference 98 I. J.